Convergent Parallel Study on Factors Affecting English Speaking Skills of Students at Mamatid National High School - Alinsunurin, Hazel (International Journal on Integrated Education, 2025)
This study examines the factors influencing the English-speaking proficiency of junior high school students at Mamatid National High School. Using a mixed-method approach, surveys and interviews explored challenges in fluency, vocabulary, pronunciation, cultural exposure, socioeconomic background, instructional techniques, motivation, and the educational environmen. Findings indicate that fluency (M = 2.27), vocabulary (M = 2.40), and pronunciation (M = 2.47) are at a low level, with minimal cultural and socioeconomic impact. Interviews highlight psychological barriers such as lack of confidence, fear of mistakes, and limited exposure to English outside school. In contrast, motivation (M = 3.68), instructional techniques (M = 3.68), and the educational environment (M = 3.68) positively impact proficiency. Teacher guidance and peer interactions were found to encourage students to practice speaking English more confidently. Students also expressed a need for more interactive and real-life opportunities to develop their speaking skills beyond the classroom. Additionally, they acknowledged that regular engagement in English conversations helped them gradually build confidence and fluency. The overall mean of 2.99 suggests that while instructional strategies and motivation improve language skills, external challenges persist. To address these, the study recommends structured vocabulary programs, pronunciation exercises, and more opportunities for real-life practice.